International aid policy: public disease control and private curative care? Política de ayuda internacional: ¿Control público de enfermedades y servicios curativos privados? - Pierre De Paepe; Werner Soors; Jean-Pierre Unger (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
Integrating disease control with health care delivery increases the prospects for successful disease control. This paper examines whether current international aid policy tends to allocate disease control and curative care to different sectors, preventing such integration. Typically, disease control has been conceptualized in vertical programs. This changed with the Alma Ata vision of comprehensive care, but was soon encouraged again by the Selective Primary Health Care concept. Documents are analyzed from the most influential actors in the field, e.g. World Health Organization, World Bank, and European Union. These agencies do indeed have a doctrine on international aid policy: to allocate disease control to the public sector and curative health care to the private sector, wherever possible. We examine whether there is evidence to support such a doctrine. Arguments justifying integration are discussed, as well as those that critically analyze the consequences of non-integration. Answers are sought to the crucial question of why important stakeholders continue to insist on separating disease control from curative care. We finally make a recommendation for all international actors to address health care and disease control together, from a systems perspective. El control de enfermedades es más factible cuando se encuentra integrado con los servicios curativos de salud. Este artículo examina si la actual política de cooperación tiende a atribuir el control de enfermedades y servicios curativos a distintos sectores, impidiendo así su integración. Tradicionalmente, el control de enfermedades fue conceptualizado en programas verticales. Eso cambió mediante la visión comprensiva de Alma Ata, para luego ser reinstaurado por el enfoque de la Salud Primaria Selectiva. Analizamos documentos de los actores más influyentes, tales como la Organización Mundial de la Salud (OMS), el Banco Mundial y la Unión Europea. Estas agencias sí tienen una doctrina en cooperación: la de colocar control de enfermedades dentro del sector público y servicios curativos dentro del sector privado, donde sea posible. Examinamos si hay un respaldo científico detrás de esta doctrina. Ponderamos los argumentos en pro de integración con las consecuencias descritas de no-integración. Determinamos cuáles son los motivos de los actores claves para seguir separando el control de enfermedades de los servicios curativos. Recomendamos, finalmente, a los actores que apoyen simultáneamente el control de enfermedades, los servicios y los sistemas de salud.